48th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2010
DOI: 10.2514/6.2010-904
|View full text |Cite
|
Sign up to set email alerts
|

Organized Streamwise Vorticity on Convex Surfaces With Particular Reference to Turbine Blades

Abstract: Experiments were conducted on the flow through a transonic turbine cascade and at subsonic speeds past a circular cylinder in cross-flow. These followed extensive work on vortex shedding behind these bodies, displaying the phenomena of energy separation at subsonic speeds; the turbine blades also exhibited exotic vortex-shedding modes in transonic flow. Surface flow visualization was undertaken on the suction surface of the turbine blade and on the circular cylinder. This was effective in providing a time-aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The lowspeed streaks near to the blade surface are also observed on the suction surface at positive incidence, implying the presence of contra-rotating vortex pairs on a convex surface. Similar structures have been found on turbine blades, and a recent summary of the evidence for their existence has been presented by Gostelow et al [41].…”
Section: Positive Incidencementioning
confidence: 72%
“…The lowspeed streaks near to the blade surface are also observed on the suction surface at positive incidence, implying the presence of contra-rotating vortex pairs on a convex surface. Similar structures have been found on turbine blades, and a recent summary of the evidence for their existence has been presented by Gostelow et al [41].…”
Section: Positive Incidencementioning
confidence: 72%
“…Surface flow visualization by Mahallati, as reported by Gostelow et al 1 , indicated strong and persistent streamwise vortical structures on the convex suction surface, as shown by the representative visualization in Fig. 1.…”
Section: Introductionmentioning
confidence: 79%
“…Halstead 6 has shown that the structures can persist through the turbulent boundary layer to the trailing edge. These fine-scale streaky structures may persist through shock interactions, laminar separation bubbles, the transition region and well into the turbulent layer 1 . Figure 2 gives an enlarged view of the vortical streaks towards the trailing edge of the turbine blade suction surface.…”
Section: Introductionmentioning
confidence: 99%
“…Surface flow visualization photographs have been analyzed from the work of a number of published experiments on blading. When examined in the same way as the surface flow visualization from the NRC cascade, two results from compressor blading 2,3 and four from turbine blading 4,11,12,13 were accessible. Figure 4 shows that these also gave reasonable agreement with the Kestin and Wood theory and experiments.…”
Section: Streamwise Vorticity Flow Visualization and Stability Thmentioning
confidence: 99%
“…Designers generally assume that streamwise vorticity of this kind is confined to these concave pressure surfaces. The authors have observed streamwise vorticity on suction surfaces, both experimentally 4 and computationally 5,6 . In this paper examples of this streamwise vorticity on convex surfaces will be considered.…”
Section: Introductionmentioning
confidence: 99%